2017
DOI: 10.1016/j.devcel.2017.09.024
|View full text |Cite
|
Sign up to set email alerts
|

MAP Kinase Cascades Regulate the Cold Response by Modulating ICE1 Protein Stability

Abstract: SUMMARY Mitogen-activated protein kinase cascades are important signaling modules that convert environmental stimuli into cellular responses. We show that MPK3, MPK4, and MPK6 are rapidly activated after cold treatment. The mpk3 and mpk6 mutants display increased expression of CBF genes and enhanced freezing tolerance, whereas constitutive activation of the MKK4/5-MPK3/6 cascade in plants causes reduced expression of CBF genes and hypersensitivity to freezing, suggesting that the MKK4/5-MPK3/6 cascade negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
309
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 389 publications
(353 citation statements)
references
References 46 publications
15
309
1
3
Order By: Relevance
“…Another piece of evidence in support of ICE1 as a regulator of CBF3 is the result recently obtained in transient expression assays in Arabidopsis protoplasts (Zhao et al 2017). The Arabidopsis protoplasts co‐transfected with ICE1 and CBF3‐LUC showed a much higher luciferase activity than the protoplasts transfected with CBF3‐LUC alone, showing that ICE1 is a positive regulator of CBF3 gene expression (Zhao et al 2017).…”
Section: Accession Numbermentioning
confidence: 92%
“…Another piece of evidence in support of ICE1 as a regulator of CBF3 is the result recently obtained in transient expression assays in Arabidopsis protoplasts (Zhao et al 2017). The Arabidopsis protoplasts co‐transfected with ICE1 and CBF3‐LUC showed a much higher luciferase activity than the protoplasts transfected with CBF3‐LUC alone, showing that ICE1 is a positive regulator of CBF3 gene expression (Zhao et al 2017).…”
Section: Accession Numbermentioning
confidence: 92%
“…In turn, OsDREB1s can promote expression of OsPLDα1 , thus creating positive feedback regulation (Huo et al ). MPK3/6 (MAPK3/6) negatively regulates cold responses in Arabidopsis by phosphorylating ICE1 following the initiation of cold signaling, resulting in ICE1 polyubiquitination and degradation (Li et al ; Zhao et al ). In contrast, OsMAPK3 enhances chilling tolerance in rice by phosphorylating OsbHLH002/OsICE1 under cold stress, which prevents its degradation (Zhang et al ).…”
Section: Cold Signal Transduction From the Plasma Membrane To The Numentioning
confidence: 99%
“…The protein kinases MPK3 and MPK6 phosphorylate ICE1, reducing its stability and transcriptional activity, which therefore negatively regulates CBF expression and freezing tolerance in plants. Conversely, the MEKK1‐MKK1/2‐MPK4 cascade promotes freezing tolerance by antagonizing the MPK3/6 pathway (Li et al ; Liu and Zhou ; Zhao et al ). During the early stages of cold stress, ICE1 is activated through OST1‐mediated phosphorylation, which inhibits its degradation.…”
Section: Cold Signal Transduction From the Plasma Membrane To The Numentioning
confidence: 99%
“…Cold-induced CBF expression is positively regulated by several transcription factors, including ICE1 (inducer of CBF expression 1), CAMTA3 (calmodulin-binding transcription activator 3), and BZR1 (brassinazole-resistant 1; Chinnusamy et al, 2003;Doherty et al, 2009;Li et al, 2017b). Recent studies showed that ICE1 protein is phosphorylated by protein kinases, including OST1 (open stomata 1) and MPK3/6 in Arabidopsis, and OsMAPK3 in rice (Ding et al, 2015;Li et al, 2017a;Zhang et al, 2017;Zhao et al, 2017;Shi et al, 2018). ICE1 is targeted for degradation after ubiquitination by HOS1 (high expression of osmotically responsive gene 1; Dong et al, 2006), whereas it is stabilized after sumoylation by SIZ1 (SAP and Miz;Miura et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…ICE1 functions as a master regulator of CBF expression (Chinnusamy et al, 2003). Under cold conditions, MPK3/6 phosphorylate ICE1 and promote ICE1 degradation in Arabidopsis, while OsMAPK3 phosphorylates and stabilizes OsICE1 in rice (Li et al, 2017a;Zhang et al, 2017;Zhao et al, 2017;Guo et al, 2018). Recent studies showed that ICE1 protein is phosphorylated by protein kinases, including OST1 (open stomata 1) and MPK3/6 in Arabidopsis, and OsMAPK3 in rice (Ding et al, 2015;Li et al, 2017a;Zhang et al, 2017;Zhao et al, 2017;Shi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%